Malpighian tubules of Rhodnius prolixus: More than post-prandial diuresis - Orchard, Ian; Al-Dailami, Areej N.; Leyria, Jimena; Lange, Angela B. (Frontiers in Insect Science, 2023)
Rhodnius prolixus, a major vector of Chagas disease, may be considered the model upon which the foundations of insect physiology and biochemistry were built. It is an obligate blood feeder in which the blood meal triggers growth, development and reproduction. The blood meal also triggers a post-prandial diuresis to maintain osmotic homeostasis. In R. prolixus, as with other insects, the Malpighian tubules play a critical role in this diuresis, and much has been learned about diuresis in R. prolixus, and in other model insects. But the post-genomic era has brought new insights, identifying functions quite apart from diuresis for Malpighian tubules. Indeed, microarrays, transcriptomes, and proteomics have revealed the major roles that Malpighian tubules play in immunity, detoxification, pesticide resistance, and in tolerance to overall stress. This is particularly relevant to R. prolixus since gorging on blood creates several challenges in addition to osmotic balance. Xenobiotics may be present in the blood or toxins may be produced by metabolism of blood; and these must be neutralized and excreted. These processes have not been well described at the molecular level for Malpighian tubules of R. prolixus. This paper will review the involvement of Malpighian tubules in immunity and detoxification, identifying new aspects for Malpighian tubule physiology of R. prolixus by virtue of a transcriptome analysis. The transcriptome analysis indicates the potential of Malpighian tubules of R. prolixus to mount a robust innate immune response, and to contribute to antioxidant production and heme detoxification.